International Business / Competing in the Global Marketplace - Hill W. Charles (Irwin Mcgraw-Hill, 2009)
This book maintains a tightly integrated flow between the chapters and identifies how real managers succeed or fail in the global economy. Introduction and Overview, Globalization, Country Differences, National Differences in Political Economy, Differences in Culture, Ethics in International Business, Nike: The Sweatshop Debate, Etc-aSketch Ethics, The Global Trade and Investment Environment, International Trade Theory, The Political Economy of International Trade, Foreign Direct Investment, Regional Economic Integration, The Politics of Trade in Steel, The Global Monetary System, The Foreign Exchange Market, The International Monetary System, The Global Capital Market, The Tragedy of the Congo, The Strategy and Structure of International Business, Entry Strategy and Strategic Alliances, Toyota: The Rise of a Global Corporation, Nestle: Global Strategy, International Business Operations, Exporting and Importing and Countertrade, Global Marketing and R&D, Global Human Resource Management, Accounting in the International Business, Financial Management in the International Business, Molex, Glossary, Index.